5 km front crawl in pool and open water swimming: breath-by-breath energy expenditure and kinematic analysis - Zacca, R.; Neves, V.; da Silva Oliveira, T.; Soares, S.; Rama, L. M. P. L.; de Souza Castro, F. A.; Vilas-Boas, J. P.; Pyne, D. B.; Fernandes, R. J. (European Journal of Applied Physiology, 2020)
Purpose: Breath-by-breath energy expenditure during open water swimming has not yet been explored in an ecological environment. This study aimed to investigate and compare energetics and kinematics of 5 km swimming, in both swimming pool and open water conditions. Methods: Through four independent studies, oxygen uptake (VO2) kinetics, heart rate (HR), blood lactate concentration ([La-]) and glucose level (BGL), metabolic power (E), energy cost (C) and kinematics were assessed during 5 km front crawl trials in a swimming pool and open water conditions. A total of 38 competitive open water swimmers aged 16-27 years volunteered for this four part investigation: Study A (pool, ten females, 11 males), Study B (pool, four females, six males), Study C (pool case study, one female) and Study D (open water, three females, four males). Results: In the swimming pool, swimmers started with an above average swimming speed (v), losing efficiency along the 5 km, despite apparent homeostasis for [La-], BGL, VO2, E and C. In open water, swimmers started the 5 km with a below average v, increasing the stroke rate (SR) in the last 1000 m. In open water, VO2 kinetics parameters, HR, [La-], BGL, respiratory exchange ratio and C were affected by the v and SR fluctuations along the 5 km. Conclusions: Small fluctuations were observed for energetic variables in both conditions, but changes in C were lower in swimming pool than in open water. Coaches should adjust the training plan accordingly to the specificity of open water swimming.